Session-RPE is a valuable internal load evaluation method in beach volleyball for both genders, elite and amateur players, conditioning and technical sessions, but limited for tactical training and games - Lupo, C.; Ungureanu, A. N.; Brustio, P. R. (Kinesiology, 2020)
This study aimed to verify the validity of session-RPE method to monitor the internal training load (ITL) in beach volleyball players by considering sessions related to different genders, competition levels (elite or amateur), and types of session (conditioning, technical, or tactical/game). Session-RPE and Edwards` methods were applied to quantify the ITLs of 12 elite (18 players; 197 individual sessions) and 12 amateur (18 players; 189 individual sessions) training sessions. Very large relationships between the two methods emerged for both competition level (Elite: r=.77; Amateur: r=.75) and gender (male: r=.76; female: r=.75) subgroups, and conditioning sessions (r=.75). Large relationships emerged for technical (r=.61) sessions, whereas tactical/ game sessions resulted only in moderate relationships (r=.36). Beach volleyball coaches could adequately use session-RPE method to monitor training for players of different genders, competition levels, and types of session, although tactical/game sessions should be considered with some caution.